2012
DOI: 10.5130/ajceb.v12i1.2358
|View full text |Cite
|
Sign up to set email alerts
|

Employee preferences for work-life benefits in a large New Zealand construction company

Abstract: The construction industry is a challenging environment in which to work, with job characteristics that are linked to work-life conflict, and it is important for its future sustainability that initiatives to support employee work-life balance are undertaken. 121 head office and site-based employees within a large New Zealand construction company rated their preferences for work-life benefits, and the results were compared with those of a similar previous (Australian) study. The most preferred work-life benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Noon and Blyton (2007) viewed WLB as the ability of individuals to successfully maintain an equilibrium with their work and non-work responsibilities, without unnecessary stresses from one weakening the satisfactory experience of the other. The study of WLB becomes necessary as a result of shift in the societal traditional model of work, requiring both genders to contribute to family common purse for upkeeps (Morrison and Thurnell, 2012), which in both domains is triggering prevalent work-life imbalance (Lewis et al, 2007). This is when WLB policies come in handy.…”
Section: Literature Review Construction Industry and Work-life Balance Of Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…Noon and Blyton (2007) viewed WLB as the ability of individuals to successfully maintain an equilibrium with their work and non-work responsibilities, without unnecessary stresses from one weakening the satisfactory experience of the other. The study of WLB becomes necessary as a result of shift in the societal traditional model of work, requiring both genders to contribute to family common purse for upkeeps (Morrison and Thurnell, 2012), which in both domains is triggering prevalent work-life imbalance (Lewis et al, 2007). This is when WLB policies come in handy.…”
Section: Literature Review Construction Industry and Work-life Balance Of Workersmentioning
confidence: 99%
“…However, most of the studies on the WLB that focused on the construction industry are conducted within the Australian or the US construction industry; interestingly, a large number of these studies were from the same authors (such as Lingard and Sublet, 2002;Francis, 2004;Lingard and Francis, 2004a, b;Lingard, 2008;Lingard et al, 2008;MacKenzie, 2008;Brown et al, 2009;Lingard and Francis, 2009;Lingard et al, 2010;Bradley et al, 2010;Malone and Issa, 2013;Malone and Issa, 2014;Lingard et al, 2015). Also, in New Zealand, Morrison and Thurnell (2012) examined construction employee preferences for work-life benefits in a large construction company and their findings suggest that work-life conflict could be associated with long working hours as well as weekend work. In spite of the huge research works and evidence that clearly showed that project managers have little or no guidance on how to maintain the family well-being and WLB of the workforce throughout the duration of a construction project (Bradley et al, 2010), none of these studies, except Malone and Issa (2013) as well as Malone and Issa (2014), examined the elements that led to enhanced organisational commitment and increasing likelihood that a female employee will stay with her employer.…”
Section: Introductionmentioning
confidence: 99%
“…An ethical organization should encourage its employees to balance work and family life (Papasolomou, 2017). It is widely accepted that work-life balance incorporates all efforts of the organization that ensure the leisure time and family life of its stakeholders, especially employees, do not come into conflict with work (Morrison and Thurnell, 2012). Thus, striking the proper balance between employees' private lives and work can contribute to building a competitive edge (Mory et al, 2016).…”
Section: Work-life Balancementioning
confidence: 99%
“…The size of the organisation also has an effect on what is feasible for employers to offer, as small businesses may find it much more difficult and expensive to offer flexible arrangements. 14 A 2012 study of employee preferences for work-life balance in a large construction company in New Zealand 16 noted that dual earner households have become the norm and the aging population has resulted in an increased demand for care of elderly relatives. Therefore, many workers are requiring and expecting more flexible working practices.…”
Section: Balance Between Work and Other Aspects Of Life -By Householdmentioning
confidence: 99%